TRANSFORMASI KUALITAS LEGISLASI: REGULATORY SANDBOX SEBAGAI SARANA PARTISIPASI PUBLIK DAN EVALUASI DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Baskoro, Aji (Badan Pembinaan Hukum Nasional, 2024)
Meaningful public participation in Indonesia's lawmaking process faces significant challenges, including low inclusivity, bureaucratic dominance, and limited opportunities for substantive societal engagement. These issues undermine the quality and relevance of legal products to societal needs and hinder their implementation. The urgency of evaluating legal frameworks has become increasingly critical to ensure that regulations are not only effective but also responsive to public aspirations. The regulatory sandbox concept offers an innovative approach by enabling policy experimentation on a small scale before full implementation, thereby improving regulatory quality while enhancing public participation. This study employs a qualitative method, utilizing literature review and policy analysis to gather data from legal documents, regulations, and previous research. It integrates statutory, comparative, and conceptual approaches. The findings reveal that regulatory sandboxes can enhance meaningful public participation through inclusive, iterative, and evidence-based policy testing, resulting in better legal outcomes. Moreover, this approach allows policymakers to identify potential risks and policy impacts before full-scale implementation. The study recommends integrating regulatory sandboxes into Indonesia's legislative system to produce adaptive, inclusive, and responsive regulations that align with societal needs.